Studies on Auditing Communication in Organizations (Acta Universitatis Danubius. Relationes Internationales, 2022)
Within any organization, communication plays a vital role in connecting different people, systems, processes and components, contributing to the fulfilment of the organizational function. Effective communication has been identified as a critical factor in determining the performance of internal audit in an organization. To achieve effective communication in audit activities, it is necessary to understand the means and channels through which communication objectives can be achieved. Communication audit is a process of exploring, examining, monitoring and evaluating the communication process within the organizational framework. Through this audit, the aim is to maintain established policies, procedures and operations, as well as to facilitate change. Similar to the financial or performance audit, the communication audit is important for any entity and should be performed regularly to keep everything in order and contribute to the overall success of the organization. If a manager does not pay attention to the communication audit, it is important that he also turns his attention to this aspect and makes the necessary changes. By carrying out the communication audit, possible improvements can be identified and changes can be made that bring added value to the organization. Thus, the communication audit is an essential process to ensure effective communication and to contribute to the long-term success of the organization.